Soil acidity and fertility status of surface soils under different land uses in Sayo district of Oromia, western Ethiopia. - Abu Regasa; Wassie Haile; Girma Abera (PLoS ONE)
Land use conversion from natural forests to grassland, plantation forests, mono-cropping coffee and croplands is a significant causes of soil degradation, leading to aggravate soil acidity and nutrient depletion. However, there is limited information regarding comprehensive effect of land use conversion on soil fertility and acidity in western Oromia Region of Ethiopia. Hence, this study aims to assess the surface soil fertility and acidity across different land use types (forest, crop, eucalyptus land, grazing land, and coffee farmland) to provide management options. A total of 60 composite soil sample were collected from four villages representing these land uses and analyzed for selected soil fertility and acidity indicators. Accordingly, sand content was highest in eucalyptus lands, whereas clay content high in forestlands. The highest soil bulk density and exchangeable acidity were observed in eucalyptus lands. The lowest pH was observed in cropland soils and the highest in forestland soils. Organic matter, total nitrogen, and available phosphorus were low in eucalyptus lands and high in forestland soils. Forest and coffee farm lands showed higher exchangeable cations, cation exchange capacity, and percentage base saturation, whereas cultivated, grazing, and eucalyptus lands obtained high level of micronutrients and exchangeable acidity. Generally, the findings indicate that land conversion has caused for lower soil pH and diminished essential macronutrients. These negative impacts on soil quality emphasize the need for sustainable soil management practices to mitigate soil degradation includes soil acidity and fertility, which significantly improve agricultural production and environmental health.